2010
DOI: 10.1039/c0sm00394h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical wrinkling patterns

Abstract: This paper reports a simple and flexible method for generating hierarchical patterns from wrinkling instability. Complex features with gradually changing topographies are generated by using the spontaneous wrinkling of a rigid membrane (titanium) on a soft foundation (polystyrene) compressed via the diffusion of a solvent. We show that the morphology of these unreported wrinkled patterns is directly related to the rheological properties of the polymer layer and the geometry of the diffusion front. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
128
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 33 publications
7
128
0
2
Order By: Relevance
“…The data suggested that the nanoscale topography may direct fi lopodia alignment, but that micro-scale patterns may be necessary for the focal adhesions to form. [ 341 ] Engelmayr et al designed an lithography. [ 336 ] Although SMCs showed no alignment on fl at substrates, SMCs cultured on grooves were elongated and parallel to the grooves, which is more similar to their in vivo morphology.…”
Section: Reviewmentioning
confidence: 99%
“…The data suggested that the nanoscale topography may direct fi lopodia alignment, but that micro-scale patterns may be necessary for the focal adhesions to form. [ 341 ] Engelmayr et al designed an lithography. [ 336 ] Although SMCs showed no alignment on fl at substrates, SMCs cultured on grooves were elongated and parallel to the grooves, which is more similar to their in vivo morphology.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, hierarchy is another desirable feature for surface patterns due to the synergic effects of hierarchical structures across multiple length scales. [10, 2327] …”
mentioning
confidence: 99%
“…For example, a wrinkling instability can be triggered in a thin elastic sheet under uniaxial extension [21][22][23], and a meniscus instability can occur when a thin layer of elastic material is confined and pulled in the out-of-plane direction resulting in a periodic array of fingers at its edges [24,25]. Moreover, it is well-known that a cavity can undergo a sudden expansion upon reaching a critical internal pressure.…”
mentioning
confidence: 99%